Research advances in integrated traditional Chinese and Western medicine for the prevention and treatment of perioperative shivering - Liu, Chaoran; Zhao, Minghe; Cao, Ruo-nan; Wang, Yuqi; Liu, Zhihui (Frontiers in Anesthesiology, 2026)
Perioperative shivering (POS) is a common complication during anesthesia recovery and has traditionally been regarded as a simple thermoregulatory response. Modern research has revealed that it involves complex mechanisms, including activation of the neuro–immune–inflammatory axis and dysfunction of mitochondrial energy metabolism. Correspondingly, traditional Chinese medicine (TCM) attributes POS to Yang Qi deficiency, a concept that aligns theoretically with modern medical understanding of impaired thermogenesis mechanisms. For the prevention and treatment of POS, Western medicine primarily employs multi-target drugs, such as dexmedetomidine, and active temperature management strategies, while TCM emphasizes holistic regulation through methods like Shenfu injection and transcutaneous electrical acupoint stimulation. By adopting an integrated treatment model combining traditional Chinese and Western medicine, we have established a closed-loop management pathway encompassing “assessment–early warning–intervention” supported by AI-assisted evaluation and intelligent TCM diagnostic methods. This approach achieves an organic unity of modern precision medicine and the holistic concept of TCM.